E-Commerce: The Mechanism of Flash Sale on Perspective Indonesia’s Positive Law and Sharia Economic Law - Purwanto, Muhammad Aji (Qawanin: Jurnal of Economic Syaria Law, 2024)
Technological developments provide easier access to marketing and buying and selling to the public. This opportunity is also used as widely as possible to market products with various online marketing strategies, one of which is flash sales. Flash sales became popular and became a buying and selling mechanism that was widely applied by online merchants. However, this leaves a question mark about the law of the flash running mechanism both in terms of Indonesia's positive law and sharia economic law in particular. The research method used in this study is qualitative research with a cross-site study approach. Primary data sources are obtained from direct searches on e-commerce platforms, while secondary data is obtained from journals and other published research results. The results of this study show that the flash sale mechanism that has been running so far in Indonesia has been in accordance with Indonesia's positive law and sharia economic law, both from normative, social, and sharia aspects itself.